Chlorophyceae, Ulvophyceae, Klebsormidiophyceae e Trebouxiophyceae filamentosas do estado de São Paulo: levantamento florístico - Díaz Valle, Karina Alejandra [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
As algas verdes filamentosas constituem um componente importante das comunidades habitantes dos ambientes dulcícolas. No entanto, a enorme plasticidade morfológica e a dificuldade de observação de vários desses organismos influíram substancialmente em sua taxonomia. Tais fatos são igualmente fundamentais na escassez de informação sobre sua ecologia O presente estudo teve como objetivo abordar a taxonomia das algas verdes filamentosas do Estado de São Paulo considerando as Chlorophyceae ‘sensu stricto’, Ulvophyceae, Klebsormidiophyceae e Trebouxiophyceae filamentosas que ocorrem no Estado. O trabalho está inserido em um projeto temático maior intitulado “Flora Ficológica do Estado de São Paulo”. Foram trabalhadas 99 amostras de distintos municípios do Estado de São Paulo. Os municípios foram escolhidos para obter uma cobertura o mais uniforme possível do território do Estado e abranger material de ambientes lênticos e lóticos em proporções equivalentes. Na abordagem taxonômica, foi inventariado o total de 69 espécies, das quais 25 pertencem à classe Chlorophyceae, 39 à Ulvophyceae, três à Trebouxiophyceae e duas à Klebsormidiophyceae. O tipo biológico constituído pelas algas filamentosas tem, em parte, certas vantagens em relação ao unicelular. Os gêneros com maior número de espécies identificadas foram Trentepohlia (15 espécies), Phycopeltis (8), Stigeoclonium (7), Microspora (6), Ulothrix (5), Chaetophora (3), Uronema, Cephaleuros e Klebsormidium (2 cada um) e os demais gêneros apresentaram apenas uma espécie cada um. As citações de Microspora lauterbornii, Microspora pachyderma, Gongrosira papuasica e Ulothrix tenuissima constituem novas referências de ocorrência no Estado de São Paulo e a de Klebsormidium scopulinum no Brasil. O tipo dominante de organização celular foi o filamentoso ramificado com ou sem mucilagem envolvente e o tipo de ambiente em que foram encontradas as algas filamentosas foi o bentônico. A informação ora apresentada reuniu dados bibliográficos e de laboratório e visou a ser uma ajuda no reconhecimento ao microscópio das algas verdes filamentosas presentes no Estado de São Paulo.

The benthic and the litoral flora primary production of lakes and other shallow water bodies represent two to three times the phytoplankton production, the contribution of the filamentous algae being of utmost relevance in such communities. They in shallow, where they usually form dense floting masses favored by the system eutrophication, and that may commonly be associated with representatives of other groups of organisms as are the cases, for instance, of Xanthophyceae and Rhodophyceae with Cyanobacteria. In addition to their role as important primary producers Present study aimed at the taxonomy of the filamentous green algae of the State of São Paulo, considering the Chlorophyceae ‘sensu stricto’, Ulvophyceae, Klebsormidiophyceae, and Trebouxiophyceae occurring in the State area. Present investigation is part of the thematic project “São Paulo State algal flora”. Ninety-nine samples from distinct municipalities of the State of São Paulo were very carefully examined. Municipalities were selected to obtain the most uniform possible coverage of the State territory, as well as lenthic and lothic environments samples in somewhat equivalent proportions. Identification of 69 species included 25 belonging to the class Chlorophyceae, 39 to Ulvophyceae, three to Trebouxiophyceae, and two to the Klebsormidiophyceae. The biological type represented by the filament has, at least in part, some advantages when compared to the unicellular. Genera with higher numbers of species identified were: Trentepohlia (15 species), Phycopeltis (8), Stigeoclonium (7), Microspora (6), Ulothrix (5), Chaetophora (3), Uronema, Cephaleuros and Klebsormidium (2 each), and the other genera with a single species each. Citations of Microspora lauterbornii, Microspora pachyderma, Gongrosira papuasica and Ulothrix tenuissima are new for the State Paulo and that of Klebsormidium scopulinum for Brasil.The dominant type of cell organization was the filamentous branched of not with or not some envolving mucilaginous sheath, and the kind of habitat in which most filamentous green algae inhabitated was dominantly benthic. Information included in this doctoral dissertation was bibliographic and produced in the laboratory and aimed at providing the students some information to recognize the State of São Paulo filamentous green algae algae at the microscope.
Filamentous Chlorophyceae, Ulvophyceae, Klebsormidiophyceae and Trebouxiophyceae from the state of São Paulo: floristic survey
Keywords: Brasil; Chlorophyceae ‘sensu amplo’; Levantamiento floristico; Taxonomia; Brazil; Floristic survey; Taxonomy